Le système narratif des « spectateurs » et leur réception en Espagne : quelques vecteurs discursifs dans le Pensador de José Clavijo y Fajardo - Klaus-Dieter Ertler (El Argonauta Español)
In our contribution, we want to take a closer look at the poetics and the narrative system of the periodical El Pensador (1762-1767), first important « spectator » in the Hispanic culture. Its author was José Clavijo y Fajardo. In the research concerning the outreaching of the European moral press, we have to consider the question to what extent this first important spectator of Spain was participating at the narrative and cultural transmission within the spectatorial network of the continent. What kind of micro-narrations are collected from other hypotextual spectators – in English, French or Italian –, and what are its imitations? Following this argumentation, we also have to ask to what extent the spectatorial narrations are linked to the Hispanic tradition.